Assessment of heat storage integration for water vapour compression heat pumps: thermodynamic and techno-economic perspectives - Seon Tae Kim; Steffen Klöppel; Eberhard Nicke; K. Malleswararao; Marc Linder; Panagiotis Stathopoulos (International Journal of Sustainable Energy)
The integrated system, consisting of a two-stage high-temperature heat pump (HTHP) and thermal energy storage (TES), has been proposed as an effective solution to reduce CO2 emissions in industrial processes effectively.The water vapour HTHP, which can supply heat at 200°C, demonstrated a coefficient of performance (COP) between 4.4 and 7.5. Two different TES systems were introduced: concrete sensible heat storage (SHS) and strontium bromide/water (SrBr2/H2O) thermochemical energy storage (TCES). While the concrete SHS is limited to temperature below 200°C, the SrBr2/H2O TCES can deliver heat between 196°C and 228°C with higher cycle efficiency. The integrated system of HTHP and SrBr2/H2O TCES achieved a net present value (NPV) of €464,559 and €182,374 over a 20-years lifespan, with internal rates of return (IRR) ranging from 15.8% to 23.6%.This HTHP and TCES system has sufficient potential to replace fossil-fuel industrial boilers, leading to significant reduction in CO2 emissions in industrial processes.